2009
DOI: 10.1097/gme.0b013e31817ee0c2
|View full text |Cite
|
Sign up to set email alerts
|

Atypical estradiol secretion and ovulation patterns caused by luteal out-of-phase (LOOP) events underlying irregular ovulatory menstrual cycles in the menopausal transition

Abstract: Many of the marked increases in ovulatory cycle E2 and cycle irregularities during the menopausal transition may be due to LOOP events and appear to be triggered by prolonged high follicular phase follicle-stimulating hormone levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 42 publications
1
85
0
3
Order By: Relevance
“…The marked increase in estradiol levels during the early follicular phase demonstrating the low ovarian reserve is due to luteal out-of-phase events and appears to be triggered by prolonged high FSH levels during the follicular phase. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The marked increase in estradiol levels during the early follicular phase demonstrating the low ovarian reserve is due to luteal out-of-phase events and appears to be triggered by prolonged high FSH levels during the follicular phase. 13 …”
Section: Discussionmentioning
confidence: 99%
“…One of them was characterized by high FSH levels, which has been associated with a slow decline in estradiol levels. 17 Similarly, Hale et al 18 reported that in 37% of the Caucasian women with menopausal owing to the loss of endogenous ovarian hormone production.…”
Section: Resultsmentioning
confidence: 99%
“…High estradiol levels with the onset of the menopausal transition could be related to a decrease in the number of ovarian follicles and the resultant impairment of a negative feedback causing elevation in FSH levels. 18,19 Another possibility is that the hypothalamic-pituitary-adrenal axis becomes less sensitive to estrogen during perimenopause.…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Hale and coauthors estimated that about a third of all menopausal transition cycles show evidence of these events, with a higher estradiol peak following the normal mid-cycle estradiol peak [4,12].…”
Section: Inaccurate Estrogen Levelsmentioning
confidence: 99%